Photobiomodulation for diabetes and its complications: a review of general presentation, mechanisms and efficacy - Wang, Keyan; Zhao, Hongwei; Zhao, Xiaoqing; Zhang, Xiaoyu; Zhang, Wei; Cheng, Yan; Ge, Jingyan (Annals of medicine (Helsinki), 2024)
Diabetes mellitus is a metabolic disease that is marked by persistent hyperglycemia due to inadequate insulin secretion or insulin resistance. Its prevalence is increasing yearly. Diabetes mellitus can lead to serious health complications that are the primary cause of mortality and disability among diabetic patients, including diabetic retinopathy, diabetic foot ulcers, diabetic peripheral neuropathy, and diabetic periodontitis, and so on. Traditional treatments for diabetes and its complications still suffer from limited clinical efficacy and high therapeutic side effects. Photobiomodulation (PBM), which utilizes low levels of red or near-infrared laser to irradiate cells and tissues, has been shown to be efficacious for a wide range of organ damage. In this study, we focus on the application of PBM in diabetes and its complications and mechanisms, as well as the advantages, disadvantages with the aim of developing new ideas for the application of PBM.